(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of intrapartum fetal distress and identify its associated factors among parturients at Ca Mau Obstetrics and Pediatrics Hospital during the 2023–2024 period. Methods: A cross-sectional descriptive study was conducted on 5,152 parturients who delivered at Ca Mau Obstetrics and Pediatrics Hospital between January 2023 and December 2024. Data on intrapartum fetal distress and associated clinical factors were extracted from medical records. Statistical associations were analyzed using univariate and multivariate logistic regression models. Results: The prevalence of intrapartum fetal distress was 12.25%. Multivariate logistic regression analysis revealed that independent risk factors for intrapartum fetal distress included: oligohydramnios (aOR = 3.20; 95% CI: 2.45–4.20), nulliparity (aOR = 1.85; 95% CI: 1.52–2.25), a history of Cesarean section (aOR = 1.38; 95% CI: 1.14–1.68), and pregnancy-related pathologies—comprising preeclampsia, gestational hypertension, and gestational diabetes (aOR = 1.42; 95% CI: 1.07–1.80), all with p < 0.05. The "residential location" factor lost its statistical significance after multivariate adjustment. Conclusions: The rate of intrapartum fetal distress is notable. Oligohydramnios, nulliparity, prior Cesarean section, and gestational pathologies are critical risk factors. These findings highlight the importance of rigorous screening and vigilant monitoring for high-risk pregnancies to facilitate early detection and timely intervention for fetal distress during labor.